Music evokes vicarious emotions in listeners - Kawakami, Ai; Furukawa, Kiyoshi; Okanoya, Kazuo (Frontiers in Psychology, 2014)
Why do we listen to sad music? We seek to answer this question using a psychological approach. It is possible to distinguish perceived emotions from those that are experienced. Therefore, we hypothesized that, although sad music is perceived as sad, listeners actually feel (experience) pleasant emotions concurrent with sadness. This hypothesis was supported, which led us to question whether sadness in the context of art is truly an unpleasant emotion. While experiencing sadness may be unpleasant, it may also be somewhat pleasant when experienced in the context of art, for example, when listening to sad music. We consider musically evoked emotion vicarious, as we are not threatened when we experience it, in the way that we can be during the course of experiencing emotion in daily life. When we listen to sad music, we experience vicarious sadness. In this review, we propose two sides to sadness by suggesting vicarious emotion.